STRUKTUR DAN KOMPOSISI VEGETASI POHON SERTA ESTIMASI BIOMASSA, KANDUNGAN KARBON DAN LAJU FOTOSINTESIS DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK - Mansur, Muhammad; Hidayati, Nuril; Juhaeti, Titi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Research the structure and composition of vegetation, biomass estimation, carbonÃ‚Â content and the rate of photosynthesis was conducted in Citalahab Central Village,Gunung Halimun-Salak National Park, West Java, on August 2010. The purpose ofÃ‚Â research to determine the components and characteristics of each tree species at theÃ‚Â study sites associated with biomass, the rate of CO2 assimilation and transpiration.Ã‚Â Results showed that, the form of classified forest area of primary forest with a littleÃ‚Â disturbed. There were recorded 337 individual trees (stem diameter > 10 cm) perÃ‚Â hectare from 71 species, 50 genera and 32 families. Lauraceae, Fagaceae, Myrtaceae,Ã‚Â Rubiaceae and Meliaceae are the 5 most common families found in the plot area, thatis dominated by Altingia excelsa, Blumeodendron elateriospermum, Ardisia zollingeri,Ã‚Â Gordonia excelsa, Tricalysia singularis, Castanopsis acuminatissima, Knema cinerea,Ã‚Â Laportea stimulant, Vernonia arborea and Dysoxylum excelsum. Estimated biomassÃ‚Â recorded of 304.5 tons dry weight / ha with a carbon content of 152.3 tons / ha ofÃ‚Â basal area of 28.89 m2/ha. Quercus oidocarpa, Litsea noronhae, Saurauia nudiflora,Ã‚Â Castanopsis argentea and Altingia excelsa has recorded the highest photosyntheticrates compared with other species. While the highest transpiration rate is owned by theÃ‚Â Macaranga triloba, Sandoricum koetjape, Prunus arborea, Urophyllum corymbosumÃ‚Â and Altingia excelsa.